Whole-body muscle magnetic resonance imaging in inflammatory myopathy with mitochondrial pathology - Cavalcante, Wagner Cid Palmeira; Silva, André Macedo Serafim da; Mendonça, Rodrigo de Holanda; Moreno, Cristiane de Araújo Martins; Proença, Bruna Moreira de Souza; Guimarães, Júlio Brandão; Ormond Filho, Alípio Gomes; Zanoteli, Edmar (Frontiers in Neurology, 2024)
Introduction. Inflammatory myopathy with mitochondrial pathology (IM-Mito) is a rare condition described in a few case series, and it is not clear whether it is a specific disease or a variant of Inclusion Body Myositis (IBM). Radiological data of IM-Mito patients has only been evaluated in one study. Aim. To analyze whole-body muscle MRI features in patients with IM-Mito compared with individuals with IBM. Methods. Fourteen IM-Mito and ten IBM patients were included. IM-Mito was defined by endomysial inflammatory infiltrate, presence of at least 1% of Cytochrome C Oxidase negative fibers, and absence of rimmed vacuoles in muscle biopsy; and IBM was defined by the presence of dystrophic muscular abnormalities, endomysial inflammatory infiltrate, and rimmed vacuoles. Patients underwent clinical evaluation and whole-body muscle MRI to determine the presence of edema, and fatty infiltration in various muscles. Results: Muscle imaging abnormalities were asymmetric in most patients with IM-Mito and IBM. Muscles with the highest average degree of fatty infiltration in both conditions were the quadriceps and medial gastrocnemius. Most patients with IM-Mito and IBM showed imaging patterns of rectus femoris relatively spared compared to other quadriceps muscles. The flexor digitorum profundus was the most affected muscle of the upper limbs in both IBM and IM-Mito. Discussion: Although the results suggest some similarities in muscle imaging features between IM-Mito and IBM, there remains uncertainty whether these two conditions are part of the same clinical spectrum.